Chief financial officer roles and enterprise risk management: An empirical based study - Stephen A. Ojeka; Alex Adegboye; Kofo Adegboye; Oluwaseyi Alabi; Mosinmileoluwa Afolabi; Francis Iyoha (Heliyon, 2019)
This study investigates the influence of CFO roles on the implementation of ERM initiatives in a sample of Nigerian financial institutions (between 2013-2017). We develop three distinct factors representing the CFO roles namely CFO power, CFO experience and CFO knowledge using principal component factoring. Like prior work, we measure ERM components simultaneously to capture the extent of sophisticated ERM system. Our findings pose that the CFO involvement in ERM implementation remains minimal while the CRO is solely responsible for ERM implementation, which could undermine cost-benefit effectiveness. Our empirical evidence reports that the sophisticated ERM only promote the market evaluation while the accounting performance is undermined. The result then contravenes the expectation that effective ERM enhances accounting performance by mitigating risk exposure. While the sophisticated ERM is significantly positive with leverage, which reveals that ERM implementation does not necessarily reduce the firm risk. This indicates that the ERM implementation remains ineffective to mitigate risks, where the CFO involvement in the ERM initiative is limited. We then advocate that CFOs should be allowed to contribute strongly on some specific aspects of ERM initiatives namely identification and analysis of key risk indicators, the financial implication of risks and integration of ERM into traditional finance activities.